2018
DOI: 10.1109/tbc.2018.2832465
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Subjective Visibility of Packet Loss Artifacts in Decoded Video Sequences

Abstract: Packet loss is a significant cause of visual impairments in video broadcasting over packet-switched networks. There are several subjective and objective video quality assessment methods focused on the overall perception of video quality. However, less attention has been paid on the visibility of packet loss artifacts appearing in spatially and temporally limited regions of a video sequence. In this paper, we present the results of a subjective study, using a methodology where a video sequence is displayed on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
(67 reference statements)
0
6
0
1
Order By: Relevance
“…Some works have evaluated the effects of packet losses in H.264/AVC and H.265/HEVC video transmission. The authors from [14] used H.264/AVC to present a subjective video degradation analysis under packet loss scenarios whereas differentiating the impact of reference and non-reference pictures. In [15], an encoding-time technique is presented for defining intra-predicted frames (i.e., IRAP) positioning in the H.264/AVC bitstream to improve packet loss resiliency.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Some works have evaluated the effects of packet losses in H.264/AVC and H.265/HEVC video transmission. The authors from [14] used H.264/AVC to present a subjective video degradation analysis under packet loss scenarios whereas differentiating the impact of reference and non-reference pictures. In [15], an encoding-time technique is presented for defining intra-predicted frames (i.e., IRAP) positioning in the H.264/AVC bitstream to improve packet loss resiliency.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Choi et al [20] studied the relationship between temporal visual masking and subjective perception quality for local flicker in compressed videos. Korhonen et al [21] observed the effect of packet loss and subjective perception in decoded videos. Multi-distortion quality evaluation methods are based on Natural Scene Statistic (NSS) [22].…”
Section: Related Workmentioning
confidence: 99%
“…Reference [7] utilized Gaussian scale mixture model to analyze the conditional entropy of reference image and distorted image, and constructed RR-VQA method on spatial scale. Although, the advantage of NR-VQA without any reference information is of great application value [8]- [10], most of the existing NR-VQA methods have the limitation of artificially extracting features, and are difficult to obtain ideal generalization performance.…”
Section: Introductionmentioning
confidence: 99%
“…The paper [ 22 ] examined the perceptibility of packet loss deficiency in the scenes’ temporal and spatial sections. End users tapped the touchscreen while the video was streamed, in the locations of artifacts.…”
Section: Related Workmentioning
confidence: 99%